A multi‐point electrical resistance measurement system for characterization of foam drainage regime and stability. Issue 9 (20th May 2014) - Park, Chanhyuk; Hermanowicz, Slawomir W.
<x xml:space="preserve">Abstract</x> Foam drainage regimes are significantly associated with the nature of the hydrodynamic resistance in foam structure. A multi‐point electrical resistance measurement technique has been applied for characterization of the drainage regimes and quantifying stability within standing foams. The capacity of the technique was confirmed by the estimation of macroscopic drainage rates for aqueous foams stabilized with sodium dodecyl sulfate. The drainage of sodium dodecylbenzenesulfonate, a commercial form of linear alkylbenzene sulfonate that is the most frequently used in household detergents was studied in detail by two complementary methods (forced and free drainage). The experimental data could be fitted using a power‐law with an exponent of 1/3 for forced drainage and of 1.0 for free drainage. These data indicate the following drainage behavior: mobile bubble surfaces, causing plug‐like flow within Plateau borders, thus dissipation mainly occurs inside the nodes. This research introduced an accurate method for quantifying foam stability that can be assessed by variations of real‐time measured foam heights that incorporate the evolution of the liquid content. © 2014 American Institute of Chemical Engineers AIChE J, 60: 3143–3150, 2014